The impact of mobile health interventions on maternal-neonatal outcomes in women with gestational diabetes mellitus: a systematic review and meta-analysis - Yang, Qiaofang; Yang, Yali; Nie, Guilan; Lou, Jianyi (Frontiers in Endocrinology, 2025)
BackgroundGestational diabetes mellitus (GDM), a prevalent complication during pregnancy, is closely associated with an elevated risk of adverse maternal and neonatal outcomes. Mobile health (mHealth) technologies have emerged as convenient tools for GDM management; however, their clinical efficacy in improving maternal and neonatal outcomes among GDM-affected pregnant individuals remains to be comprehensively evaluated.ObjectiveThe study aims to evaluate the effectiveness of mHealth interventions in improving maternal and neonatal outcomes among pregnant individuals with GDM.MethodsThis study systematically searched the PubMed, Web of Science, Scopus, Cochrane Library, and EMBASE databases from their inception to July 23, 2025. Two researchers independently screened the studies, extracted data, and assessed quality. All data analyses were performed using STATA 17.0 software.ResultsCompared with routine care, mHealth interventions significantly reduced the risk of cesarean section (OR 0.76, 95% CI 0.63–0.91) and emergency cesarean (OR 0.55, 95% CI 0.39–0.77) among women with GDM. Additionally, a significant reduction in the risk of composite neonatal complications was observed (OR 0.63, 95% CI 0.44–0.89). Furthermore, mHealth interventions significantly improved 2-hour postprandial blood glucose levels (SMD −0.36, 95% CI −0.53 to −0.19). A trend toward reduced gestational weight gain was also noted in the mHealth intervention group (SMD −0.37, 95% CI −0.83 to 0.08).ConclusionmHealth interventions can reduce the risk of cesarean section rate and emergency cesarean section, as well as the risk of composite neonatal complications. mHealth interventions may also improve two-hour postprandial blood glucose control in pregnant women with GDM and can effectively supplement conventional clinical care for GDM.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251149505.